(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2018)
The occupation of Tapanuli district was an objective of Dutch colonial settlement in the Indonesian archipelago. The expansion of the area was not only due to political factors but also due to vast economic ambition. This was evident from the trade monopoly of coffee from the beginning of Dutch occupation in the area. The colonial government’s desire for the economy was gratified by the implementation of coffee forced-farming in Tapanuli. The forced-farming system created huge profits for the treasury of the Dutch colonial government. The colonial exploitation was not confined to coffee forced-farming only but also extended to the local people, who were forcibly exploited for their labour as coolies to carry the coffee beans from remote storehouses to the port. The suffering of the local people worsened when Tapanuli district was categorised as a taxpayer district by the end of 19th century.